Design and and creation of a gender literacy program for the Center for Women's Studies Library of the University of the Philippines - Montes, Merselle F.; Dar Juan, Elijah John F. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
This is a study focused on the creation and design of a library-based gender literacy program based in the University of the Philippines Center for Women's Studies Library. The study sought to discover the different considerations in creating the program in the said institution. The study also sought to discover what the students wanted to know about gender issues, their preferred media for learning, and their potential responsiveness to such a program. The study narrowed down the vast pool of knowledge on gender issues into the essential topics needed by the University's students and create modules that would equip them with the information they need and want to know. The study was qualitative in nature, with the goal of discovering the in-depth ideas and views of its participants. The study had various phases of data gathering. The views of the Institution were determined through interviews and constant consultation throughout the course of the research, while the views of the students were collected through focus group discussions. Consultations with the UP Diliman Gender Office were also done by the researcher.
The results show that, as a small special library, the UPCWS library had a lot of specific considerations, like the time duration of the program, the shortage of staff, and the lack of teaching facilities. The students, while still holding on to a lot of misconceived notions about gender and sex from their previous experiences, showed open-mindedness and an awareness of how their beliefs may not have been absolute truth but were social constructs dictated by society. The results of the focus group discussions also show that the more the students were exposed to various gender issues and people of different gender identities and the more they learned about these particular issues, the more they tolerated and accepted behavior different from their own. These results all factored in the type of materials the researcher created for the program. The study concluded with the selection of four major topics for inclusion in the program: 1) basic concepts of gender literacy; 2) gender roles, women empowerment, and gender equality; 3) LGBT awareness and acceptance; and 4) sexual harassment on campus. The researcher created modules for these topics by adapting well established, internationally recognized, and freely distributed manuals on gender training into literacy materials suited and adjusted for the needs and specific characteristics of the UP CWS library.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Literacy programs -- Philippines -- Quezon City; Gender-based analysis -- Philippines -- Quezon City